Fish as Indicators of Disturbance in Streams Used for Snorkeling Activities in a Tourist Region - Teresa, Fabricio Barreto [UNESP]; Romero, Renato de Mei [UNESP]; Casatti, Lilian [UNESP]; Sabino, Jose (Springer, 2011)
A set of metrics that reflect various aspects of population and fish community structure in streams used for snorkeling was evaluated in the tourist region of Bodoquena Plateau, Brazil, with the purpose of biomonitoring the impacts of such activities. Observations were made while snorkeling in two sites (active = with tourism; inactive = without tourism) and along the gradient of daily tourist activity (before, during and after the passage of tourists) in two streams. Five metrics discriminated active from inactive sites: (i) the abundance of Crenicichla lepidota and (ii) the incidence of reproductive activity in Crenicichla lepidota which were greater in inactive sites, regardless the gradient of daily tourist activity; (iii) the feeding pattern of Prochilodus lineatus, which differed among sites and along the gradient of daily tourist activity; (iv) the abundance of Moenkhausia bonita, which was higher in the active sites and significantly increased along the gradient of daily tourist activity in one stream but decrease along the gradient in other stream; (v) the abundance of Hyphessobrycon eques, which was greater in inactive sites, regardless the gradient of daily tourist activity. With the exception of metric "iv", the metrics were mediated by the reduction in habitat structural complexity due to snorkeling disturbance. The definition of these metrics is relevant because the degradation of ecosystem structural elements is one of the main impacts of recreational activities on aquatic environments. The easy recognition of target species and high water transparency throughout the year ensures the feasibility of these metrics in monitoring programs and may be applied by technicians after quick guides and training.
Keywords: Tourism; Biomonitoring; Anthropogenic impacts; Skin diving